Experiences of teen fathers’ relationship with significant others in Vaalbank, Mpumalanga Province, South Africa - Koketso, Matlakala Frans (Penerbit Universiti Kebangsaan Malaysia, 2019)
This study explored the phenomenon teen fatherhood in Vaalbank of Mpumalanga Province in South Africa. Teenage fatherhood is a global problem that receive less attention from scholars as teenage mothers are the ones who enjoys the benefits of being researched. As such, the experiences of teenage fatherhood remain unscrutinised and overlooked. This paper sought to explore the experiences of teen fathers’ relationship with significant others in Vaalbank, Mpumalanga Province. The author used qualitative approach and exploratory-descriptive Afrocentric research design exploring the experiences of teen fathers from seven participants through semi-structured interviews. The study discovered that the participants received support from their parents and their peers when they told them that they are teenage fathers. Others highlighted that, through conversing with their peers, they had learnt that, as fathers, they needed to get jobs. However, the community was not as understanding as the teenage fathers’ family and peers. Community members expect a grown-up man to be a father and not a teenager t. This article shows that teenage fathers receive stereotypical views from their community as they are seen as deviant and lacking societal norms.